Pre-Coated Ce/Co-Coated Steel: Mitigating Cr Vaporization, Increasing Corrosion Resistance at Competitive Cost. (2nd June 2015) - Falk Windisch, Hannes; Mertzidis, Ioannis; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : Cr vaporization and oxide scale growth are probably the two most detrimental degradation mechanisms associated to Cr2 O3 -forming alloys as interconnect material in SOFC. Both issues can be improved by the application of coatings. However, the use of coatings increase material cost. To reduce coating costs it is suggested that large amounts of steel can be coated before shaping the pre-coated material into an interconnect. The present study investigates the effectiveness of thin Ce and Co coatings on the cost effective steel AISI 441 with respect to Cr vaporization and corrosion resistance. Furthermore, the effect of mechanical deformation of the coated steel is examined. The results revealed that when the pre-coated steel is deformed, large cracks are formed. However, upon exposure those cracks can heal forming a continuous surface oxide rich in Co and Mn. As an effect of the rapid healing, no increase in Cr vaporization was measured.